P2.182 Male Genital Dermatoses in HIV. (13th July 2013) - Shim, T N; Hawkins, D; Muneer, A; Minhas, S; Freeman, A; Jameson, C; Francis, N; Dinneen, M; Bunker, C B
Abstract : Background: Little information exists about penile squamous cell carcinoma (PSCC), penile carcinoma in situ (PCIS) and male genital lichen sclerosus (MGLSc) in HIV. Methods: A retrospective review of case notes was performed on HIV-positive men who had presented to specialised Male Genital Dermatoses Clinics between May 2011 and February 2013. Results: 39 men were identified. The mean age at diagnosis was 48 years (range 26 – 71 years). The mean diagnostic delay was 20 months (range 1 – 72 months). 35 were uncircumcised at presentation (4 were circumcised at birth/childhood). The majority of the cases had PCIS (21); 8 had MGLSc, 2 had lichen planus (GLP), 2 had PSCC and the remaining cases had more than one diagnosis (1 had PSCC and MGLSc, 2 had PSCC and PCIS, 3 had PCIS and MGLSc); 6 men had co-existing anal dysplasia (2 had anal SCC); 36 were on ARVs. All genital dermatoses were treated according to our conventional practise. The majority (31) is in remission; 6 have residual disease and receive ongoing treatment (1 GLP, 1 MGLSc and 4 PCIS); 2 have been lost to follow-up; most (32) have been circumcised (including 4 circumcised at birth/childhood). 1 has a short foreskin hence circumcision is not indicated. Conclusion: Advances in ARV treatment have improved the survival of individuals with HIV. This has led to increased interest in long-term morbidities, including cancer. MGLSc and PCIS can progress to invasive cancer. The risk of PSCC in HIV despite ARV treatemnt is x5–6. The presence of the foreskin confers cancer risk. Uncircumcised HIV men should be counselled about the risk of PSCC. There may be an argument for prophylactic circumcision in high-risk cases such. Certainly, clinicians should enquire about the genital health of HIV-positive men and undertake regular (ano)genital examination at follow-up.